Efektivitas Pendistribusian Pupuk Bersubsidi kepada Masyarakat - Suhartin Akadji; Nur Insani; Rusmulyadi Rusmulyadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the effectiveness of subsidized fertilizer distribution to farmers in Gorontalo Regency. The allocation system follows a regulatory procedure starting from the Minister of Agriculture Regulation, followed by the Governor’s Decree, and finally by the Regent/Mayor’s Decree, which determines fertilizer allocation down to farmer groups. However, the implementation in the field faces several issues, including fertilizer shortages, prices exceeding the government-set retail price (HET), and misuse of distribution mechanisms. Using a normative-empirical legal research method, the study finds that the ineffectiveness of the subsidized fertilizer program is mainly due to inaccurate data collection and distribution, as well as the suboptimal use of the Farmer Card (Kartu Tani), often hampered by technical problems such as inactive cards. An evaluation based on the